PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. TELKOM AKSES WITEL GEMA (WILAYAH TELKOM GRESIK MADURA) DI KOTA GRESIK - Kusumaningrum, S.Si., M.M., Dini; Yuliani, Windy Dwi (Fakultas Ekonomi Universitas Gresik, 2018)
This study aims to examine and prove the influence of leadershipstyle and organizational culture on the performance of employees ofPT. Telkom Access Witel GEMA (Telkom Region Gresik Madura) inGresik City. This research uses quantitative approach with multiplelinear regression analysis. Population in this research is employees ofPT. Telkom Witel Access GEMA (Telkom Gresik Madura Region) inGresik City, amounting to 230 people in the Year 2017. To determinethe number of samples using the formula slovin so that obtained asample of 146 respondents and data collection is done by spreading thequestionnaire. The results of this study indicate that leadership stylehas a large and significant influence on employee performance. Whileorganizational culture has a positive and significant influence on theperformance of employees of PT. Telkom Access Witel GEMA (TelkomRegion Gresik Madura) in Gresik City. This means that the leadershipstyle and organizational culture simultaneously affect the performanceof employees of PT. Telkom Access Witel GEMA (Telkom RegionGresik Madura) in Gresik City.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475670